Strategi Bauran Pemasaran dengan Analisis SWOT pada Kedai Cokelat Klasik - Idha Dwi Firdayanti; Sonja Andarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research was conducted at the Kedai Cokelat Klasik which is a business engaged in the culinary business sector as the object of research. The purpose of this study is to identify and analyze the marketing mix strategy implemented based on the SWOT analysis by Kedai Cokelat Klasik. The results of the SWOT analysis method are used as the basis for determining the marketing mix strategy that can be carried out by Kedai Cokelat Klasik. The research method used is a qualitative type with descriptive analysis which refers to the concept of the 4P marketing mix, namely Product, Price, Place and Promotion. Data collection techniques were carried out by means of in-depth interviews, participatory observation and field research. The analytical method used is the SWOT analysis method with the stages of compiling the IFAS and EFAS matrices, determining the SWOT quadrant and SWOT matrix. From the results of the study, it can be concluded that Kedai Cokelat Klasik is in quadrant I position. It can be concluded that the marketing mix strategy applied by SWOT analysis is an aggressive strategy, namely by maximizing its strengths to take advantage of existing opportunities. Keywords: Marketing Mix Strategy, SWOT Analysis, IFAS Matrix, EFAS Matrix